Case studies to enhance graduate employability : 2015 government as employer. - Kinash, Shelley; Crane, Linda; Judd, Madelaine-Marie; Knight, Cecily; McLean, Matthew; Mitchell, Kirsty; Dowling, David; Schwerdt, Ros; Lovell, Caroline (Australia. Office for Learning and Teaching, 2015)
Case study from a project that addressed how educators and employers can best support graduate employability. The aims of the project (commissioned in December 2013) were to: (1) achieve a greater clarity on the issues, challenges and contexts of graduate employability; (2) identify and review the strategies that have been successfully used to address these challenges; (3) create opportunities for the diverse stakeholder groups to share their perspectives; and (4) promote strategies that may be used by the various stakeholders to collaborate on improving graduate outcomes. The case study focuses on graduate employability in government.